Civil society in an age of uncertainty : institutions, governance and existential challenges - Chaney, Paul; Jones, Ian (Author of Driving public service transformation and innovation through the Invest to Save Fund) (Civil Society and Social Change Ser., 2022)
This book explores how the uncertainties of the 21st century present existential challenges to civil society. Presenting original empirical findings, it highlights transferable lessons that will inform policy and practice in today's age of uncertainty.